Rhamnopyranoside-Based Fatty Acid Esters as Antimicrobials: Synthesis, Spectral Characterization, PASS, Antimicrobial, and Molecular Docking Studies - Abul Fazal Muhammad Sanaullah; Puja Devi; Takbir Hossain; Sulaiman Bin Sultan; Mohammad Mohib Ullah Badhon; Md. Emdad Hossain; Jamal Uddin; Md. Abdul Majed Patwary; Mohsin Kazi; Mohammed Mahbubul Matin (Molecules, 2023)
The most widely used and accessible monosaccharides have a number of stereogenic centers that have been hydroxylated and are challenging to chemically separate. As a result, the task of regioselective derivatization of such structures is particularly difficult. Considering this fact and to get novel rhamnopyranoside-based esters, DMAP-catalyzed di-O-stearoylation of methyl α-l-rhamnopyranoside (3) produced a mixture of 2,3-di-O- (4) and 3,4-di-O-stearates (5) (ratio 2:3) indicating the reactivity of the hydroxylated stereogenic centers of rhamnopyranoside as 3-OH > 4-OH > 2-OH. To get novel biologically active rhamnose esters, di-O-stearates 4 and 5 were converted into six 4-O- and 2-O-esters 6–11, which were fully characterized by FT-IR, 1H, and 13C NMR spectral techniques. In vitro antimicrobial assays revealed that fully esterified rhamnopyranosides 6–11 with maximum lipophilic character showed better antifungal susceptibility than antibacterial activity. These experimental findings are similar to the results found from PASS analysis data. Furthermore, the pentanoyl derivative of 2,3-di-O-stearate (compound 6) showed better antifungal functionality against F. equiseti and A. flavus, which were found to be better than standard antibiotics. To validate the better antifungal results, molecular docking of the rhamnose esters 4–11 was performed with lanosterol 14α-demethylase (PDB ID: 3LD6), including the standard antifungal antibiotics ketoconazole and fluconazole. In this instance, the binding affinities of 10 (−7.6 kcal/mol), 9 (−7.5 kcal/mol), and 7 (−6.9 kcal/mol) were better and comparable to fluconazole (−7.3 kcal/mol), indicating the likelihood of their use as non-azole type antifungal drugs in the future.